Remittances and Economic Growth: Case for Asian Countries - Dwi Handoyo, R; Bangkit Simanjuntak, R (KnE Social Sciences, 2019)
This research aims to analyze the influence of remittance of migrant on economic frowth of the origin country. We also scrunitize the affect of capital, population ratio, the ratio of school participation, and the ratio of exports on economic growth in eight largest receiving countries of remittance in Asia which are India, China, Bangladesh, Philippines, Indonesia, South Korea, Pakistan and Sri Lanka using generalized method of momments (GMM). The results show that remittance have a positive and significant influence on economic growth. The increasing number of remittance shipments will have an effect on the country’s economic growth. Keywords: economic growth, remittance, generalized method of momments